Enhancement of low field magnetoresistance by chemical interaction in bulk composites La0.7Sr0.3MnO3/SrMeO3 (Me=Ti, Zr) - Shlyakhtin, OA; Shin, KH; Oh, YJ (AMER INST PHYSICS, 2002)
In order to enhance low field magnetoresistance (LFMR) of bulk manganite materials, two series of composites, La0.7Sr0.3MnO3/SrTiO3 and La0.7Sr0.3MnO3/SrZrO3, have been prepared by thermal processing of mixed powders. For both series annealing of pelletized mixtures over certain critical temperature leads to the substantial enhancement of LFMR for compositions close to theoretical percolation threshold. At higher processing temperatures enhanced MR values are observed for composites with higher La0.7Sr0.3MnO3 content, while compositions with a lower amount of manganite become insulating. The magnitude of enhanced MR remains almost the same within the same series, but the value of enhancement is substantially different for composites, containing SrTiO3 and SrZrO3 (1.5% and 2.5% at H=100 Oe, respectively). Similar dependencies are observed for coercive field values. Observed shift of the enhancement boundary during thermal processing and significant dependence of SrZrO3 lattice parameters versus components ratio and composite processing temperatures (1100-1200 degreesC) show at substantial chemical interaction in these composites. (C) 2002 American Institute of Physics.
Keywords: YTTRIA-STABILIZED ZIRCONIA; GRAIN-BOUNDARIES; THIN-FILMS; LA0.7CA0.3MNO3; LA; SRZRO3